PENGARUH PELATIHAN KERJA, MOTIVASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BPR SARI JAYA SEDANA KLUNGKUNG, BALI - Ni Kadek Rina Sepriyani; Ni Made Dwi Puspitawati; Gde Bayu Surya Parwita (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Human resources are an important factor in controlling the progress or decline of a company. One of the factors that influences a company's success is employee performance. Based on the results of observations and interviews conducted with several employees of PT. BPR Sari Jaya Sedana found a problem that employee performance was not able to provide maximum results. This can be seen from the existence of several employees who are less able to achieve the given work targets. Therefore, this research was carried out to determine the effect of work training, motivation and work discipline on employee performance at PT. BPR Sari Jaya Sedana. The population in this study were all employees at PT BPR Sari Jaya Sedana, the number of employees was 30 people. The sample selection method used was a saturated sampling technique (census), where all members of the population were sampled, so the total sample used was 30 people. The types of data used in this research are quantitative data and qualitative data, while the data sources use primary data and secondary data. This research uses a number of data collection methods consisting of observation, interviews and questionnaires. The data that has been collected is processed using the SPSS version 25.0 for Window program. To analyze the data, five methods were used which included research instrument tests, classical assumption tests, multiple regression analysis, determination coefficient tests (R2), and also the t statistical test. The results of this research show that (1) job training has a positive and significant effect on employee performance. This means that if job training increases, the performance of PT BPR Sari Jaya Sedana employees will also increase. (2) motivation has a positive and significant effect on employee performance. This means that if motivation increases, the performance of PT BPR Sari Jaya Sedana employees will also increase and (3) work discipline has a positive and significant effect on employee performance. This means that if work discipline increases, the performance of PT BPR Sari Jaya Sedana employees will also increase.